Risk of cardiovascular events during labor and delivery associated with acute ambient temperature changes - Jenna Kanner; Danielle R. Stevens; Carrie J. Nobles; Matthew C.H. Rohn; Sandie Ha; Tuija Männistö; Marion S. Ouidir; Pauline Mendola (Elsevier, 2021)
Purpose: We assessed acute risk of cardiovascular events at labor/delivery with exposure to ambient temperatures during the week prior to delivery in a low-risk population. Methods: A case-crossover design evaluated 191 women with cardiovascular events at labor/delivery in the Eunice Kennedy Shriver National Institute of Child Health and Human Development Consecutive Pregnancies Study (Utah, 2002-2010). Using conditional logistic regression models, we estimated the odds ratio (OR) and 95% confidence interval (CI) for each 1 °Celsius (1.8°F) increase in the warm season (May-October) or decrease in the cold season (November-April) in the week prior to delivery compared to two weeks prior and after delivery. Results: Cardiovascular events during delivery included acute myocardial infarction (n = 1), stroke (n = 29), heart failure (n = 7), cardiac arrest (n = 118), and unspecified (n = 39). Cardiovascular event risk increased by 9% (95% CI: 1.02, 1.18) for every 1 °C increase in average temperature in the week prior to delivery during the warm season and increased 6% (95% CI: 1.00, 1.13) for every 1 °C decrease during the cold season. Conclusion: Acute temperature changes in the week prior to delivery were associated with increased risk of cardiovascular events at labor/delivery.